Rebirth [compact disc] - Childs, Billy; Childs, Billy (Mack Avenue, 2017)
On his new album Billy Childs reaches back to the start of his almost astoundingly varied musical experience, leading a small jazz band of state-of-the-art musicians with his piano playing.